2001
DOI: 10.1002/1618-2863(200108)1:2<97::aid-elsc97>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Cavitation/Constructed Wetland Reactors for Treatment of Chlorinated and Non-Chlorinated Organics

Abstract: Mitigation strategies can be implemented to decrease chlorinated and non‐chlorinated organic exposures to biota of aquatic receiving systems thereby reducing associated risks. In this work, we investigated the concept of coupling a physical/chemical reactor (i.e. a cavitation reactor) with a biological reactor (i.e. a constructed wetland) in an effort to efficiently transform PCE, TCE, and petroleum in freshwater into non‐toxic chemical forms or concentrations. Rates of TCE degradation due to cavitation ranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…With new molecules being discovered almost on a continuous basis, some of which are biorefractory, the efficacy of biological oxidation techniques has decreased and the course of new inventions was focused on developing alternative techniques for wastewater treatment (Mantzavinos et al, 1997; Otal et al, 1997). It should also be noted that some of these methods were aimed at merely reducing the toxicity level of the effluent or, in other words, at increasing the biodegradability of the effluent so that biological oxidation can be used more efficiently (Gulyas et al, 1995; Hess et al, 1998; Mastin et al, 2001). The reduction in the toxicity achieved at the primary stage of the treatment also affects the efficacy of biological oxidation used subsequently.…”
Section: Introductionmentioning
confidence: 99%
“…With new molecules being discovered almost on a continuous basis, some of which are biorefractory, the efficacy of biological oxidation techniques has decreased and the course of new inventions was focused on developing alternative techniques for wastewater treatment (Mantzavinos et al, 1997; Otal et al, 1997). It should also be noted that some of these methods were aimed at merely reducing the toxicity level of the effluent or, in other words, at increasing the biodegradability of the effluent so that biological oxidation can be used more efficiently (Gulyas et al, 1995; Hess et al, 1998; Mastin et al, 2001). The reduction in the toxicity achieved at the primary stage of the treatment also affects the efficacy of biological oxidation used subsequently.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies actually deal with the treatment of PCE in CW. Mastin et al (2001) reported similar removal efficiency of 99% for PCE in a vertical upflow anaerobic wetland, but without any information on metabolite formation. In a study by Amon et al (2007), an upflow vertical wetland (670 m 2 , 1.14 m depth) was fed with PCE (0.205 µmol L −1 ) contaminated groundwater for 21 months of operation.…”
Section: Temporal Development Of Pce Degradation Patternsmentioning
confidence: 99%
“…At this facility, the potential stormwater contact pollutants included volatile organic compounds and metals. Many researchers have focused on work removing metals from stormwater ͑Dunbabain and Bowmer 1992; Karpiscak et al 2001;Scholes et al 1998;Scholz 2004;Vymazal and Krasa 2003;Walker and Hurl 2002;Weis and Weis 2004͒ or treatment of volatile organic compounds ͑Keefe et al Mastin et al 2001͒. The problems facing this facility also integrated aspects of urban hydrology, which has been extensively studied ͑Berezowsky 1995; Carleton et al 2000;Helfield and Diamond, 1997;Koob et al 1999;Scholes et al 1999;Shutes et al 1997͒.…”
Section: Considered Optionsmentioning
confidence: 99%